OPTIMIZATION OF MODES OF ELECTRIC POWER SYSTEMS BY THE ALGORITHM OF ARTIFICIAL BEE COLONY - Bozorov , Afzalbek Turg‘unaliyevich (Educational Research in Universal Sciences, 2023)
Optimal planning of modes of electric power systems (EPS) is a complex problem of nonlinear mathematical programming with many different constraints in the form of equalities and inequalities. Therefore, its solution by traditional algorithms is often associated with some simplifications, which generally lead to a decrease in the effect of optimization.